Marine protected areas : tools for sustaining ocean ecosystems (National Academy Press, 2001)
Although the ocean-and the resources within-seem limitless, there is clear evidence that human impacts such as overfishing, habitat destruction, and pollution disrupt marine ecosystems and threaten the long-term productivity of the seas. Declining yields in many fisheries and decay of treasured marine habitats, such as coral reefs, has heightened interest in establishing a comprehensive system of marine protected areas (MPAs)-areas designated for special protection to enhance the management of marine resources. Therefore, there is an urgent need to evaluate how MPAs can be employed in the United States and internationally as tools to support specific conservation needs of marine and coastal waters. Marine Protected Areas compares conventional management of marine resources with proposals to augment these management strategies with a system of protected areas. The volume argues that implementation of MPAs should be incremental and adaptive, through the design of areas not only to conserve resources, but also to help us learn how to manage marine species more effectively.